Contrary to Psychological and Popular Opinion, There Is No Compelling Evidence That Older Adults Are Disproportionately Victimized by Consumer Fraud. (July 2014) - Ross, Michael; Grossmann, Igor; Schryer, Emily
According to psychological and popular opinion, older persons are especially susceptible to consumer fraud. Research on cognitive and affective aging reveals age-related changes that could increase the vulnerability of older persons to consumer fraud. However, this research does not show that consumer fraud actually is more prevalent among older persons. In generalizing from laboratory findings of cognitive decline to age differences in the prevalence of consumer fraud, psychologists may underestimate the influence in everyday life of possible protective factors associated with old age, including increased experience and changes in goals, lifestyle, income, as well as purchasing and risk behaviors. We review evidence on the prevalence of consumer fraud and conclude that there is no clear indication that it is more prevalent among older persons. Aggregating across all consumer frauds, there is evidence that consumer fraud is less common among older persons than adults of other ages. This evidence is potentially flawed, however, because of failings inherent in the methodologies. In the absence of irrefutable data, it is premature to conclude that consumer fraud is less prevalent among older adults, but it is also premature to conclude that consumer fraud is more prevalent among older persons, as is assumed in conventional and psychological wisdom.